Balier’s French Narcissistic Theory of Ageing: Developments and Perspectives - Rexand-Galais, Franck; Le Goff, Johane (Frontiers in Psychology, 2020)
Claude Balier's narcissistic theory of aging may be one of the pillars of French psycho-gerontology, but it is certainly not set in stone. On closer inspection, instead of being just minor variations on the same theme, the three stages of its development are structured around different references and make different assumptions. Some even contradict each other. Balier’s theory nevertheless finds unity in its non-involutionary view of aging. Narcissism and narcissistic destiny are given a central role, thus calling into question the notion that the paradigmatic function of transference neurosis can account for neurosis in old age. For more than 40 years, Balier’s innovative notions have been the subject of many and sometimes divergent extensions in French psycho-gerontology.